EKSTRAKSI ZAT WARNA ALAMI DAUN KETAPANG (TERMINALIA CATAPPA) UNTUK PEWARNA SABUN PADAT BERBAHAN DASAR MINYAK JELANTAH - Anisa Afifatul Aziizah; Siti Khuzaimah (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
Indonesia is a tropical area where various types of plants can thrive, one of the tropical trees, namely ketapang, is widely planted on the side of the road, in front of schools or in the yard of the house. The leaves of the ketapang tree have dense leaves every day, dry leaves can wither twice a year so that they become waste that is only thrown away or burned without being used properly. The content of ketapang leaves contains flavonoids, alkaloids and phenolics which contain antioxidants, anthocyanins and antibacterials. From this content, leaf extract of ketapang can be used as a natural dye in the manufacture of solid soap. The purpose of this research is how to extract ketapang leaves so that they have high economic value that can be used as natural dyes in the manufacture of solid soap. Ketapan leaf extract was tested for absorbance values using a uV-Vis spectrovoteer at a wavelength of 400 nm. Ketapang leaf extract with variations in mass of material, namely 20, 25, and 30 grams and extraction time of 24, 48 and 72 hours using ethanol as a solvent. The results obtained were the highest reduction in water content at a temperature of 800C, the highest absorbance yield was at a mass of 30 grams and an extraction time of 72 hours was 0.752 g/100 mL